SMART VILLAGE DESIGN USING INDONESIAN GOVERNMENT ENTERPRISE ARCHITECTURE - Salma Ida Anindita; Berlian Maulidya Izzati; Fitriyana Dewi (STKIP PGRI Tulungagung, 2022)
Almost all aspects of life require information technology, starting from aspects of primary, secondary, and tertiary needs. Digital technology and innovation can support quality of life, higher standards of living, better public services for the community, and better use of resources to become new opportunities for a rural value chain in terms of better products and processes. Smart village is the concept of developing an independent village by providing services. Implementing smart villages will be the right solution to building a formidable and sustainable smart city to improve the quality of public resources and services. IGEA framework (Indonesian Government Enterprise Architecture Framework) is designed to build an enterprise architecture at the Indonesian government level to support the development of IT services to be better, more efficient, and effective. The phases used in architectural design using IGEA are the Preliminary Phase, Architecture Vision, Business architecture, Data Architecture, Application Architecture, and Technology Architecture. This study aims to analyze, design, and produce a blueprint for Enterprise Architecture by applying the smart village concept to overcome public service problems and improve the quality of apparatus resources and accountable governance in public services. The scope of this research is only in the preliminary phase of the business architecture. The result is architecture principle, goals, vision and mission, policy and regulation, solution concept diagram, and improvement of twelve business processes, and public service catalog.